2022
DOI: 10.3390/cryst12101393
|View full text |Cite
|
Sign up to set email alerts
|

A Lection in Humbleness: Crystallization of Chiral and Zwitterionic APIs Baclofen and Phenibut

Abstract: Crystallization and multicomponent crystal formation of active pharmaceutical ingredients Baclofen and Phenibut with dicarboxylic acid co-formers are discussed. The crystallization process of several crystalline entities is elucidated via single crystal—as well as powder X-ray—diffraction, followed by thermal analysis and phase stability studies over time. Both APIs form increasingly complex crystalline phases with co-formers malic and tartaric acid, where phase purity of a desired compound is not necessarily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
2
6
0
Order By: Relevance
“…However, mechanochemically prepared systems may have higher amorphicity, more crystalline defects, or morphology changes that can affect product properties [ 61 , 62 , 63 ]. Our group observed similar findings for Baclofen and Phenibut, where multicomponent forms received through grinding or solvent-based methods showed different thermal properties in some cases [ 57 ]. Over the years, various theories on crystallization mechanisms during grinding have been proposed.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…However, mechanochemically prepared systems may have higher amorphicity, more crystalline defects, or morphology changes that can affect product properties [ 61 , 62 , 63 ]. Our group observed similar findings for Baclofen and Phenibut, where multicomponent forms received through grinding or solvent-based methods showed different thermal properties in some cases [ 57 ]. Over the years, various theories on crystallization mechanisms during grinding have been proposed.…”
Section: Introductionsupporting
confidence: 57%
“…Thus, it appears that an additional crystallization product forms here that are not yet characterized by single-crystal diffraction. Past works have shown that 4 tends to form non-pure phases more commonly, which is likely due to comparatively high lattice energy that makes the formation of multicomponent phases unfavorable [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 2 behaves rather different than 1 in two key aspects: firstly, 2 does not form a stable hydrate as racemic 1 does. 85,86 Contrary to the latter, 2 -hydrate transitions to anhydrous 2 quickly, suggesting a preferable form in the anhydrous species. Furthermore, experimental observations conducted in the presented work suggest a higher stability of 2 as compared to 2 : 3 .…”
Section: Resultsmentioning
confidence: 92%
“…Wang et al reported strategies of additive-induced and liquid-assisted mechanochemical GABA polymorph control [ 42 , 44 ], followed by Lamkowski et al, who discussed the pH influences on the stabilization of II -GABA in 2022 [ 45 ]. A plethora of pharmaceutically active ingredients (APIs) are derived from GABA, such as pregabalin, phenibut, baclofen, and gabapentin, which have all been discussed regarding their crystal structure over time [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. Gabapentin stands out as a reliable medication, popularly used for nearly 30 years.…”
Section: Introductionmentioning
confidence: 99%